Article Review: Skin Diseases in Dromedary Camels - Gharban, Hasanain A.J. (Newinera Publisher, 2024)
The dromedary camel (Camelus dromedarius) is a significant livestock species in several nations located in desert and semi-arid regions of Asia, Northern and Eastern Africa, South America, and the high highlands of the Andes. In Iraq, the FAO figures of 2014 indicate that there are around 65,000 camels, all of which belong to the species Camelus dromedarius and have a single hump. Camels are the primary source of sustenance for all Bedouin clans and villages in various ecological zones in Iraq. This dependence involves the usage of camel milk, meat, leather, and wool. Furthermore, camels have been used as beasts of burden, means of transportation, and mounts. Camels, typically grown in their native desert environment, experience significant stress due to the prolonged dry season. This stress makes them vulnerable to many illnesses and health issues. Historically, owing to little research on camel ailments, doctors believed that camels were immune to many disease-causing causes. Scientific evidence has shown that camels, like other livestock or maybe even more so, are vulnerable to the same disease-causing viruses that impact other animal species. Camels often suffer from illnesses that are challenging to manage because to their non-specific symptoms and similarity to diseases seen in other ruminant animals. Additionally, camels have some resistance to some infections. This research attempts to provide a concise description of the most frequently seen skin disorders in dromedary camels in Iraq.